Kepatuhan Pencegahan Pencemaran Peraturan Menteri Perhubungan Nomor 24 Tahun 2022 dan Konflik Regulasi: Analisis Sosio-Legal Kewajiban Stabilitas Peraturan Menteri Perhubungan Nomor44 tahun 2021 pada Armada SHSB (Single hull single bottom) - Wahyudi Rahmat Ryan Dani; Irfan Faozun; Chandra Faozun Purnama (Yayasan Literasi Sains Indonesia, 2026)
Compliance with pollution prevention obligations (PM 24/2022) and ship stability standards (PM 44/2021) in Indonesia has created a critical juridical conflict, with both regulations sharing a compliance deadline of July 1, 2026. This study aims to analyze the socio-legal implications of this regulatory ambiguity on the operational continuity of the Single Hull Single Bottom (SHSB) fleet. Utilizing a qualitative case study method, this research triangulates data through legal document analysis and focus group discussions with 12 key informants from Regulators, Ship Operators, and Classification Societies. The main findings reveal a significant three-way interpretative disconnection Regulators focus on the philosophical intent of safety policies, Operators experience investment paralysis due to financial uncertainty regarding costly retrofits versus mandatory phase-outs, and Classification Societies rigidly apply both rules textually without discretion. This misalignment creates a systemic risk of simultaneously grounding 53 tanker vessels, threatening the national energy supply chain and the economic stability of archipelagic regions. This study concludes that the issue extends beyond technical matters, representing a normative coordination failure between law in books and law in action. Consequently, the research recommends the issuance of a Circular Letter by the Director General of Sea Transportation as a technical instrument to provide clear audit exemptions, thereby restoring legal certainty and preventing maritime logistics disruption before the 2026 deadline.